Synthesis of stable lithium modified mesoporous catalyst for oligomerization of biodisel-drive glycerol to diglycerol - Ayoub, M. (Italian Association of Chemical Engineering - AIDIC, 2015)
Biodiesel is an alternative fuel option for future, which comes from pure renewable resources. The rapid growth of the biodiesel industry will result in overproduction of low value glycerol and create a superfluity of this impure by-product. The synthesis of lithium modified mesoprous catalyst for dilyglycerol production via oligomerization of low value biodiesel drive glycerol is reported. This reaction of selective glycerol conversion to diglycerol was studied in a heterogeneous catalysis under solvent free system, using alkaline mesoporous catalysts. Mesoporous materials SBA-15 was synthesized by using P123 and TEMOS as the template. Lithium in the form of LiOH was loaded over prepared SBA-15. The basic strength of prepared samples of SBA-15 was found increasing but structure of mesoporous was found destroying after LiOH loading. The mesoporous structure of prepared SBA-15 was found stable after doping it with 20 alumina before loading with LiOH. This stability of mesoporous structure was observed very sensitive with alumina doping. These samples were well characterized by surface area, pore volume, pore size, basic strength, and transmission electron microscope (TEM) measurement of prepared samples. The glycerol conversion and dilyglycerol production yield was noted maximum 92 and 74.5 over prepared stable lithium modified SBA-15 catalysts. Industrially, the findings attained in this study might contribute towards promoting the biodiesel industry through utilization of its by-products. Copyright Â© 2015, AIDIC Servizi S.r.l.,.